Pengembangan Strategi Pembelajaran Kontekstual Mata Kuliah Fotografi Pendidikan Program Studi Teknologi Pendidikan Universitas Negeri Jakarta - Muhammad Fatih Abiyyu; robinson situmorang; murti kusuma wirasti (Universitas Negeri Jakarta, 2021)
This development research aims to produce a product in the form of Rencana Perkuliahan Semester (RPS) by implementing contextual learning strategies and learning unit modules in the Education Technology Study Program at the State University of Jakarta. In this research development refers to the Dick & Carey model which consists of: identifying Instructional Goal (s), Conduct Instructional Analysis, Analyze Learners and Context, Write Performance Objective, Develop Instrument Assessment, Develop Instructional Strategy, Develop and Select Instructional Materials, Design and Conduct Formative Materials Evaluation of Instruction, and Revise Instruction. This development research product has gone through the formative evaluation stage, namely expert review and one to one. The results of the Expert Review from the learning design expert obtained a value of 3.75 (very good). material expert of 2.9 (good), and from media expert got a score of 3.85 (very good). Then the user evaluation (one to one) was conducted to users namely lecturers and students. One to one evaluation by lecturers received a score of 3.57 (very good) and evaluations conducted by students get a value of 3.7 (very good) .Based on these results, it can be concluded that the Rencana Perkuliahan Semester product in Education photography courses and learning unit modules is very good.